Oxytocin Manipulation Alters Neural Activity in Response to Social Stimuli in Eusocial Naked Mole-Rats - Faykoo-Martinez, Mariela; Mooney, Skyler J.; Holmes, Melissa M. (Frontiers in Behavioral Neuroscience, 2018)
The social decision-making network is a conserved neural circuit that modulates a range of social behaviors via context-specific patterns of activation that may be controlled in part by oxytocinergic signalling. We have previously characterized oxytocin’s influence on prosociality in the naked mole-rat, a eusocial mammalian species, and its altered neural distribution between animals of differing social status. Here, we asked two questions: 1) do patterns of activation in the social decision-making network vary by social context and 2) is functional connectivity of the social decision-making network altered by oxytocin manipulation? Adult subordinate naked mole-rats were exposed to one of three types of stimuli (three behavioral paradigms: familiar adult conspecific, unfamiliar adult conspecific, or familiar pups) while manipulating oxytocin (three manipulations: saline, oxytocin, or oxytocin antagonist). Immediate early gene c-Fos activity was quantified using immunohistochemistry across social decision-making network regions. Network analyses indicated that the social decision-making network is conserved in naked mole-rats and functions in a context-dependent manner. Specific brain regions were recruited with each behavioral paradigm suggesting a role for the nucleus accumbens in social valence and sociosexual interaction, the prefrontal cortex in assessing/establishing social dominance, and the hippocampus in pup recognition. Furthermore, while oxytocin manipulation was generally disruptive to coordinated neural activity, the specific effects were context-dependent supporting the hypothesis that oxytocinergic signalling promotes context appropriate social behaviors by modulating co-ordinated activity of the social decision-making network. ACC=Anterior cingulate cortex, AH=Anterior hypothalamus, AntPVN=Anterior paraventricular nucleus, AON=Anterior olfactory nucleus, BLA=Basolateral amygdala, BNST=Bed nucleus of the stria terminalis, CeA=Central amygdala, CG=Cingulate cortex, CA1=Cornu ammonis 1, CA2=Cornu ammonis 2, CA3=Cornu ammonis 3, Caudate=Caudate putamen, dDG=dorsal dentate gyrus, IL=Infralimbic cortex, LS=Lateral septum, MeA=Medial amygdala, MOB=Main olfactory bulb, MS=Medial septum, NAcc=Nucleus accumbens, PG=periaqueductal grey, PIC=Piriform cortex, PO=Pre-optic area, PostPVN=Posterior paraventricular nucleus, PrL=Pre-limbic cortex, SON=Supraoptic nucleus, Tu=Olfactory tubercle, vDG=Ventral dentate gyrus, VMH=Ventromedial hypothalamus, VP=Ventral pallidum, VTA=Ventral tegmental area